Readiness of Teachers to Use Intelligent Search Systems in the Digital Educational Environment - Abdrakhmanova, S.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
This research article discusses the implementation and integration of artificial intelligence-based search engines in higher education institutions, as well as theoretical and practical aspects of the implementation of such systems in Kazakhstan. It describes the current practice, challenges and potential of future achievements in the field of AI, as the modernization of education has become a global trend, especially in the field of digital technologies. Examples of existing AI-based search engines in the field of education and science are also provided. Despite this, there are challenges in ensuring that all universities effectively use available open educational resources (OER) and intelligent search engines in the educational process, which could revolutionize the design of an open digital educational environment for teachers. It should be noted that the research article deeply examines the aspects of using artificial intelligence-based search engines in the field of science, namely the potential of advanced technologies and the latest pedagogical innovations. The study provides an overview and analysis of existing artificial intelligence search engines in the scientific field that provide solutions to pedagogical problems.
Педагогтардың сандық білім беру ортасында зияткерлік іздеу жүйелерін пайдалануға дайындығы
Готовность педагогов к работе с интеллектуальными поисковыми системами в цифровой образовательной среде
Keywords: search engine; digital environment; OER; digital competence; teacher; readiness; artificial intelligence; higher education; educational resources